Caries prevalence and associated factors in children from public versus private schools: Cross-sectional study (Revista Contexto & Saúde, 2024)
Introduction: Childhood caries remains a major public health issue in Brazil’s impoverished communities. Although government-sponsored programs have targeted improvement of oral health in children from public schools, more information is needed on the effectiveness of these programs. Objective: The objective was to analyze the prevalence and factors associated with caries in children aged 5 and 12 years in public versus private schools. Methods: This cross-sectional study included 857 children aged 5 (n=509) and 12 years (n=348) who attended public (n=416) or private (n=441) schools in Patos, PB-Brazil. Between March–September 2018 we examined caries from this study population using the DMFT/dmft index and obtained data on its demographics, toothbrushing frequency, socioeconomic status and schools’ oral health program and services via questionnaires. Statistical analyses were performed using multiple logistic regression (p
Keywords: dental caries; pediatric dentistry; preventive dentistry; public health practice